Hubungan Dukungan Keluarga Dalam Diit Hipertensi Dengan Frekuensi Kekambuhan Hipertensi Pada Lansia Di Wilayah Kerja Posyandu Desa Blimbing Sukoharjo - Suwandi, Yusuf Denirvan, Abi Muhlisin, SKM., M.Kep (2016)
THE RELATIONSHIP FAMILY SUPPORT OF HYPERTENSION DIET WITH FREQUENCY RECURRENCE OF HYPERTENSION IN ELDERLY IN WORK AREA POSYANDU BLIMBING SUKOHARJO Abstracts Hypertension is a disease whose prevalence is quite high and continues to rise in Indonesia. Uncontrolled hypertension is a hypertensive condition that the handling is not done optimally and usually blood pressure greater than 140/90 mmHg. If hypertension is not treated optimally will result in the return of symptoms recurrence of hypertension. So it can be at risk of having a stroke or myocardial infarction. Hypertension is a degenerative disease that is often experienced by the elderly. elderly is the decrease in endurance. So that elderly people who have health problems in dire need of family support. Family support is one part of the family duties to care for sick relatives. Lack of family support in caring for the elderly who suffer from hypertension often lead to recurrence or return of symptoms of hypertension. This study aims to determine the relationship of family support in hypertension diet with kakambuhan frequency of hypertension in the elderly in the Work Area Posyandu Blimbing Sukoharjo. This research is a descriptive penilitian correlative with cross sectional approach. The study population was all the elderly who suffer from hypertension and had a relapse in the Work Area Posyandu Blimbing Sukoharjo. A sample of 34 elderly by using total sampling technique. Collecting data using questionnaires family support amounting to 19 items by category of good and less good, as well as using the checklist frequency of recurrence of hypertension by category sometimes relapse that relapses ≤ 2 times in 3 months and serng relapse that relapses> 2 times in 3 months. Analyzed using the Spearman rank correlation test. Speaman rank correlation test results showed that the relationship of family support in hypertension diet with a recurrence of hypertension in the elderly in the Work Area Posyandu Blimbing Sukoharjo (count r = - 0.410) with (p = 0.016). The conclusion in this study is there is a relationship of family support in hypertension diet with a recurrence of hypertension in the elderly in the Work Area Posyandu Blimbing Sukoharjo. The results of this study are expected to increase in the diet hypertension family support for the elderly who suffer from hypertension and may lower the frequency of recurrence of hypertension in the elderly. Keywords: Family Support, Recurrence hypertension, Elderly